Lemental Ratio Controlled Semiconductor Type of Bismuth Telluride Alloy Thin Films. Issue 12 (December 2015) - Shuai, Liu; Fei, Liu; Xiaoqi, Zhu; Yu, Bai; Dayan, Ma; Fei, Ma; Kewei, Xu
Abstract: Bismuth telluride alloy thin films were prepared on quartz substrates by co-sputtering method and thermally annealed at 423∼623 K, for 1 h. It is found that the Te/Bi ratio decreases upon thermal annealing, indicating the loss of Te as a result of evaporation. This leads to the transformation of Bi2 Te3 thin films from n-type to p-type, and consequently the change of Seebeck coefficient from the negative value to the positive one. In addition, the grain growth occurs during thermal annealing, in particular, at higher temperature, as a result, both the electrical conductivity and the seebeck coefficient are increased.